The Prophet Muhammad’s Leadership: An Islamic View - Saeed Al-Olaqi, Fahd Mohammed Taleb (Advances in Social Sciences Research Journal, 2015)
<!--[if gte mso 9]> Normal 0 false false false MS JA AR-SA <![endif]--><span style="font-size: 11.0pt; line-height: 115%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'MS Mincho'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-GB; mso-bidi-language: AR-SA;" lang="EN-GB">The article is a logical and positive argument to William Montgomery Watt’s Muhammad: Prophet and Statesman,<span style="font-size: 11.0pt; line-height: 115%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'MS Mincho'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-GB; mso-bidi-language: AR-SA;" lang="EN-GB">[1] which represents to the Western reader imperfect depiction about the Prophet Muhammad’s successful statesmanship as part of his Prophethood. This claim represents a secular ground that the Prophet Muhammad has politically founded Islam. In spite of misunderstanding of Islamic leadership as being religious, Prophet Muhammad cannot be branded as a statesman. It is fairly clear that the Prophet's leadership is a worldly method which is applicable in real life even without being an Islamic state. The Prophet Muhammad’s techniques in his leadership played a significant part in achieving his goal to deliver the message of Islam to the world. He had all the necessary leadership attributes for success in every aspect of life. Allah the Almighty says, ‘Most certainly, you have in the messenger of Allah an excellent pattern (of behaviour) <!--[if gte mso 9]> Normal 0 false false false MS JA AR-SA <![endif]--> The article is a logical and positive argument to William Montgomery Watt’s Muhammad: Prophet and Statesman,<span style="font-size: 12.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">[1] which represents to the Western reader imperfect depiction about the ProphetMuhammad’s successful statesmanship as part of hisProphethood. This claim represents a secular ground that the Prophet Muhammad has politically founded Islam. In spite of misunderstanding of Islamic leadership as being religious, Prophet Muhammad cannot be branded as a statesman. It is fairly clear that the Prophet's leadership is a worldly method which is applicable in real life even without being an Islamic state. The Prophet Muhammad’s techniques in his leadership played a significant part in achieving his goal to deliver the message of Islam to the world. He had all the necessary leadership attributes for success in every aspect of life. Allah the Almighty says, ‘Most certainly, you have in the messenger of Allah an excellent pattern (of behaviour)’<span style="font-size: 12.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-GB; mso-bidi-language: AR-SA;" lang="EN-GB">[2] <span style="font-size: 10.0pt; line-height: 115%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'MS Mincho'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-GB; mso-bidi-language: AR-SA;" lang="EN-GB">[1]William Montgomery Watt (1909 –2006) is a Scottish historian, an Emeritus Professor in Arabic and Islamic Studies at the University of Edinburgh. Watt is one of the foremost non-Muslim interpreters of Islam in the West. He is an enormously powerful scholar in the field of Islamic studies. Watt's comprehensive biography of the Prophet Muhammad, "Muhammad at Mecca" (1953) and "Muhammad at Medina" (1956) are considered to be pioneer studies in such a field. Watt’s Muhammad: Prophet and Statesman, is designed for the general audience, not for university dons. <span style="font-size: 10.0pt; line-height: 115%; font-family: 'Calibri',sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'MS Mincho'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-GB; mso-bidi-language: AR-SA;" lang="EN-GB">[2]The Glorious Qur’ān: 33:21. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->